The Possessor and the Possessed: Handel, Mozart, Beethoven and the Idea of Musical Genius - Kivy, Peter 1934-2017 (New Haven, CT Yale University Press, 2001)
The concept of genius intrigues us. Artistic geniuses have something other people don't have. In some cases that something seems to be a remarkable kind of inspiration that permits the artist to exceed his own abilities. It is as if the artist is suddenly possessed, as if some outside force flows through them at the moment of creation. In other cases genius seems best explained as a natural gift. The artist is the possessor of an extra talent that enables the production of masterpiece after masterpiece. This book explores the concept of artistic genius and how it came to be symbolised by three great composers of the modern era: Handel, Mozart, and Beethoven.
Keywords: Handel, George Frideric -- 1685-1759; Mozart, Wolfgang Amadeus -- 1756-1791; Beethoven, Ludwig van -- 1770-1827; 18th Century (1701-1800); 19th Century (1801-1900); Genius; Composer; Europe